HUBUNGAN SPIRITUALITAS, RELIGIUSITAS DENGAN TEKANAN DARAH PADA LANSIA HIPERTENSI - Kodariyah Kodariyah; Syirli Anggriani (Poltekkes Kemenkes Jambi, 2023)
ABSTRACT Background: Increasing age can cause blood pressure in the elderly to increase, the arteries will thicken which creates a greater risk of developing hypertension. The recommended management of hypertension with complementary therapy is to increase spirituality and religiosity. Increasing spirituality and religiosity is used to reduce stress, pressure, depression which can cause an increase in blood pressure. This study aims to determine whether there is a relationship between spirituality, religiosity and blood pressure in elderly people with hypertension at the Putri Ayu Community Health Center. Method: This analytical survey research using a cross-sectional approach was carried out on the elderly population with hypertension at the Putri Ayu Community Health Center. 132 samples were taken using purposive sampling. Data was taken from a form of questionnaire that was in accordance with the inclusion Criteria. Data analysis using Chi Square. Result: The research results showed that 72.7% of Respondent with Stage 1 hypertension, and 27.3% of Respondent with Stage II hypertension. With high spirituality level of 75.8% and high level of religiosity is 76.5%. The results of bivariate analysis showed that there was a relationship between spirituality and religiosity and blood pressure in hypertensive elderly (P value = 0.000). Conclusion : There is a Relationship between Spirituality and Religiosity with Blood Pressure in Hypertensive Elderly at the Putri Ayu Community Health Center. It is recommended that the Community Health Center provide education to increase spirituality and religiosity for the elderly. Keywords : Hypertension, Elderly, Religiosity, Spirituality, Blood Pressure